VD_FINDINFO Décision / 2009 / 217 vom 26. August 2009 - VD Tribunal cantonal (2009)
RADIATION DU RÔLE, PROCÈS DEVENU SANS OBJET | 1 al. 1 LAMal, 50 al. 1 LPGA, 50 LPGA, 61 let. a LPGA, 61 let. g LPGA, 117 al. 1 LPA-VD, 55 LPA-VD, 94 al. 1 let. c LPA-VD